Hubungan Antara Skor Intracerebral Hemorragahe (ICH) dengan Mortalitas Pasien Perdarahan Intracerebral di RSU Royal Prima Medan - Sari, Dian Puspita; Harahap, Alvin Abrar; Bangun, Primta (Syntax Literate, 2025)
Intracerebral hemorrhage (ICH) is a form of hemorrhagic stroke with a high mortality rate. Assessment of severity using the ICH score is crucial for predicting prognosis and determining patient treatment priorities in hospitals. This study aims to determine the distribution of ICH patients based on the Glasgow Coma Scale (GCS) score, ICH volume, the presence of intraventricular hemorrhage (IVH), age, and location of the hemorrhage, and to analyze the relationship between ICH scores and patient mortality at Royal Prima Medan Hospital. This study used an observational-analytical design with a cross-sectional approach. The study population was all patients diagnosed with ICH during the study period, while a sample of 96 patients was obtained using the Lameshow formula. Data were collected through medical records and analyzed univariately and bivariately using the Chi-Square test. The results showed that most patients had a mild GCS score (53.1%), mild ICH volume (33.3%), and no intraventricular hemorrhage (52.1%). The largest age group was >60 years (56.3%), with the most common bleeding location being the right parietal (13.5%). The mortality rate reached 50%. Statistical tests showed no significant association between ICH score and mortality (p = 0.101), although clinically there was a trend towards an increased risk of death as the ICH score increased. Most patients presented with mild clinical conditions, but mortality remained high in more severe ICH scores. This study recommends improved early detection, more comprehensive radiological recording, and routine application of the ICH score as a prognostic tool in the management of patients with intracerebral hemorrhage.